On a nonlinear model in domains with cavities arising from cardiac electrophysiology. (1st October 2022) - Beretta, Elena; Cerutti, M Cristina; Pierotti, Dario
Abstract: In this paper we deal with the problem of determining perfectly insulating regions (cavities) from boundary measurements in a nonlinear elliptic equation arising from cardiac electrophysiology. With minimal regularity assumptions on the cavities, we first show well-posedness of the direct problem and then prove uniqueness for the inverse problem.